Association of Thymbra capitata essential oil and chitosan (TCCH hydrogel): a putative therapeutic tool for the treatment of vulvovaginal candidosis†. (3rd February 2013) - de‐Oliveira, A. Palmeira‐; de‐Oliveira, R. Palmeira‐; Gaspar, C.; Salgueiro, L.; Cavaleiro, C.; de‐Oliveira, J. Martinez‐; Queiroz, J.A.; Rodrigues, A.G.; Figueiredo, Ana Cristina; Rubiolo, Patrizia
ABSTRACT In this study we tested the anti‐Candida effect of Thymbra capitata essential oil (EO) plus chitosan and developed a new therapeutic tool. The classical check‐board methodology was used to determine the anti‐Candida activity that results from product association. The incorporation of T. capitata EO in a chitosan hydrogel, using lactic acid as the solvent, resulted in the TCCH hydrogel. Its anti‐Candida activity was studied by using 18 Candida strains, according to the CLSI M27‐A3 micromethod and the lethal effect according to the protocol proposed by Canton et al. The TCCH activity in acidic conditions corresponding to a healthy vaginal pH (4.5) was also tested. Its anti‐Candida activity upon pre‐formed biofilm metabolism and biomass was tested using the semi‐quantitative XTT reduction assay and the crystal violet staining assay, respectively. The hydrogel interaction with the yeast surface was shown by confocal microscopy. TCCH hydrogel presented an acidic nature, compatible with the vaginal pH. The association of both natural products revealed an additive effect upon Candida and TCCH hydrogel showed to be active upon both Candida planktonic and biofilms. No cell invasion was observed. Being a new product with an acidic nature compatible with the vaginal environment and presenting a potent effect upon Candida planktonic and biofilm cells, TCCH hydrogel could represent a valuable tool for the treatment of vulvovaginal candidosis. Copyright © 2013 John Wiley & Sons, Ltd.